Our Post-Moral Future? (Existential Analysis: Journal of the Society for Existential Analysis, 2010)
Murray responds to champions of a new brain reading technology who claim that it will combat future crimes before they happen. Murray argues that the concept of crime prevents us from identifying one proactively, and suggests an array of other problems with the scientists’ assumptions and methodology. She places the scientists’ announcement within the context of what she claims is a wider movement towards revising the laws of nature to cohere with new technological manipulations of the natural world. Over-emphasizing biological and genetic influences on human behaviour implies a deterministic model of human nature that paves the way for conservative changes to society, especially forms of technological social control. Promoting the deterministic model re-locates social evils in the individual or within human nature itself, while distracting attention from social and institutional inequities. Sartre’s critique of the ways in which humans attempt to obscure the extent of their freedom makes existentialism as relevant as ever. Moreover, the anguished wont to unburden ourselves of the dreaded responsibility that freedom implies makes us ever more susceptible to those who furnish excuses for bad behaviour and attribute it to natural causes. Murray concludes that the deterministic model of human nature implied by champions of “pre-cog” crime prevention is antithetical to the very meaning of “crime” as we know it. Crime and punishment depend upon free human agency, a cornerstone of liberal democracy. By re-defining criminal acts as involuntary and inevitable, proponents of the new technology merely fabricate a dubious demand for the product they hope to supply.
Keywords: John Dylan-Haynes; brain-reading technology/mind-reading technology